Advertisements
Advertisements
Question
Matrices of different orders can not be subtracted.
Options
True
False
Solution
This statement is True.
Explanation:
For addition and subtraction, the order of the two matrices should be same.
APPEARS IN
RELATED QUESTIONS
if `[[9,-1,4],[-2,1,3]]=A+[[1,2,-1],[0,4,9]]`, then find the matrix A.
If A = diag (2 − 59), B = diag (11 − 4) and C = diag (−6 3 4), find: A − 2B
Given the matrices
`A=[[2,1,1],[3,-1,0],[0,2,4]]` , `B=[[9,7,-1],[3,5,4],[2,1,6]]` `and C=[[2,-4,3],[1,-1,0],[9,4,5]]`
Verify that (A + B) + C = A + (B + C).
Find matrix A, if `[[1 2 -1],[0 4 9]]`
`+ A = [[9 -1 4],[-2 1 3]]`
\[A = \begin{bmatrix}2 & 3 \\ - 1 & 0\end{bmatrix}\],show that A2 − 2A + 3I2 = O
Show that the matrix \[A = \begin{bmatrix}2 & 3 \\ 1 & 2\end{bmatrix}\]satisfies the equation A3 − 4A2 + A = O
If `[x 2] [[3],[4]] = 2` , find x
If \[\begin{bmatrix}x & x - y \\ 2x + y & 7\end{bmatrix} = \begin{bmatrix}3 & 1 \\ 8 & 7\end{bmatrix}\] , then find the value of y.
If \[\begin{bmatrix}9 & - 1 & 4 \\ - 2 & 1 & 3\end{bmatrix} = A + \begin{bmatrix}1 & 2 & - 1 \\ 0 & 4 & 9\end{bmatrix}\] , then find matrix A.
If \[\begin{bmatrix}a - b & 2a + c \\ 2a - b & 3c + d\end{bmatrix} = \begin{bmatrix}- 1 & 5 \\ 0 & 13\end{bmatrix}\] , find the value of b.
If matrix \[A = \begin{bmatrix}2 & - 2 \\ - 2 & 2\end{bmatrix}\] and A2 = pA, then write the value of p.
If \[\begin{bmatrix}a + 4 & 3b \\ 8 & - 6\end{bmatrix} = \begin{bmatrix}2a + 2 & b + 2 \\ 8 & a - 8b\end{bmatrix}\] , write the value of a − 2b.
If \[A = \begin{bmatrix}0 & 2 \\ 3 & - 4\end{bmatrix}\] and \[kA = \begin{bmatrix}0 & 3a \\ 2b & 24\end{bmatrix}\] then the values of k, a, b, are respectively
Find matrix X so that `x ((1,2,3),(4,5,6)) = ((-7,-8,-9),(2,4,6))`.
If \[A = \begin{bmatrix}2 & - 1 \\ - 1 & 2\end{bmatrix}\] and I is the identity matrix of order 2, then show that A2= 4 A − 3 I. Hence find A−1.
Matrix subtraction is associative
If A = `[(1, 2),(-2, 1)]`, B = `[(2, 3),(3, -4)]` and C = `[(1, 0),(-1, 0)]`, verify: (AB)C = A(BC)
Let A = `[(1, 2),(-1, 3)]`, B = `[(4, 0),(1, 5)]`, C = `[(2, 0),(1, -2)]` and a = 4, b = –2. Show that: a(C – A) = aC – aA
Let A = `[(1, 2),(-1, 3)]`, B = `[(4, 0),(1, 5)]`, C = `[(2, 0),(1, -2)]` and a = 4, b = –2. Show that: (A – B)C = AC – BC